2017
DOI: 10.1177/1558944717726135
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Osteotomies of Phalangeal and Metacarpal Malunions Using Patient-Specific Guides: CT-Based Evaluation of the Reduction Accuracy

Abstract: BACKGROUND Surgical planning of corrective osteotomies is traditionally based on conventional radiographs and clinical findings. In the past 10 years, 3-dimensional (3D) preoperative planning approaches with patient-specific guides have been developed. However, the application of this technology to posttraumatic deformities of the metacarpals and phalangeal bones has not yet been investigated. Our goal was to evaluate the feasibility of the surgical application to the latter and to evaluate the extent and prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Hirsiger et al [8] reported satisfactory outcomes, correcting phalangeal and metacarpal malunions using 3D patient-specific templating, a similar technique to our case. However, their series only included one intra-articular malunion, which consisted of an metacarpal base intra-articular malunion [8].…”
Section: Discussionsupporting
confidence: 75%
“…Hirsiger et al [8] reported satisfactory outcomes, correcting phalangeal and metacarpal malunions using 3D patient-specific templating, a similar technique to our case. However, their series only included one intra-articular malunion, which consisted of an metacarpal base intra-articular malunion [8].…”
Section: Discussionsupporting
confidence: 75%
“…The here presented type of measurements have been used to verify the accuracy of bone malunion correction in orthopaedic surgery. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…The here presented type of measurements have been used to verify the accuracy of bone malunion correction in orthopaedic surgery. 18,19 So far, there is only one experimental study directly comparing the accuracy between PSI and optical navigation with respect to bone tumor surgery: While both achieved acceptable accuracy, surgeons described intra-operative use of PSI as simpler. Moreover, the average time required for resection was significantly lower in the PSI group.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided 3D surgery planning with the implementation of 3D printed patient-specific templates, including the information for drill, cutting, and re-positioning in the different bony parts (the so-called patient-specific instruments = PSIs), seems to be a promising tool to optimize the intervention results in these cases. So far, a limited number of studies, case series, and case reports considering upper extremity deformities have investigated the relevance of this technique and found promising results [ 1 4 , 6 13 ]. However, the comparability of these studies is limited due to the various methods, software, and hardware tools used for 3D planning and printing.…”
Section: Introductionmentioning
confidence: 99%